Requirements for a Technology-Supported Students’ Career Selection Model: Insights from Social Cognitive Career Theory - Tuhame, Moses Kamondo; Kayondo, Barbara Naluwadda; Habinka Dorothy Basaza, Annabella; Maiga, Gilbert (Universitas Bina Darma, 2024)
Inappropriate career choices at the secondary level contribute to challenges like high university dropout, delayed course completion, and frustration. While ICTs play a growing role in career guidance due to evolving technologies, many aspects of technology-supported systems remain under-researched. This study addresses the gap by investigating the requirements of a technology-supported career model for secondary school students basing on the Social Cognitive Career Theory. A mixed-methods approach was used, in line with the pragmatism paradigm. A survey was conducted on a random sample of 784 Ugandan students from 15 secondary schools and 1 university, while qualitative data was collected through interviews with 17 purposively selected key informants. SPSS and NVIVO softwares were used for data analysis. EFA and CFA confirmed the factor structure of instrument scores. Study results revealed that all the 7 variables under study were valid. Results indicate that career decisions are influenced by parental guidance, role models, financial constraints, media exposure, and self-efficacy, with students generally showing moderate confidence in their career choices but facing challenges related to external pressures and decision-making complexity. Therefore, requirements for the technology-supported model should include student personality assessment, digital internships, success stories, workshops, discussion forums and detailed information about career progression.